Pengaruh Akuntabilitas dan Transparansi Terhadap Kinerja Keuangan dengan Konsep Value for Money pada Dinas PUPR Kabupaten Bone Bolango - Moh. Rizki Usman; Mattoasi; Victorson Taruh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the effect of accountability and transparency on financial performance with the Value for Money concept in the Bone Bolango Regency PUPR service, both partially and simultaneously. Type The type of method used in this research is a quantitative method with data collection techniques using questionnaire surveys and observation. The number of respondents in this research was 63 respondents consisting of Service Heads, Secretaries, Treasurers and all PUPR service employees of Bone Bolango Regency. The results of this research show that accountability and transparency towards financial performance with the Value for Money concept in the Bone Bolango Regency PUPR service have an effect both partially and simultaneously with a determinant value of 62.9% while the remaining 37.1% is explained by other variables not studied. in this research.